Control of Ni-Ti phase structure, solid-state transformation temperatures and enthalpies via control of L-PBF process parameters. (June 2022) - Chekotu, Josiah Cherian; Goodall, Russell; Kinahan, David; Brabazon, Dermot
Graphical abstract: Highlights: Density of Ni-Ti controlled via control of L-PBF process parameters. Element concentration in Ni-Ti alloy controlled via L-PBF settings. Enthalpy and phase change temperatures controlled via L-PBF settings. Thermal variation in samples linked to resulting sample density. Thermal variation is samples controlled via alignment of print direction. Abstract: In this work, nitinol samples were produced via Laser Powder Bed Fusion (L-PBF) in the horizontal and vertical orientations with systematic variations in laser power, scan speed and hatch spacing parameters. Increased density was positively correlated with increased laser power, scan speed and hatch spacing for the horizontally built samples but not for the vertically built samples. A smaller difference in the average temperature within a printed layer, associated with the vertically built samples, was linked with reduced porosity and reduced porosity variability between samples. Control of the L-PBF parameters was found to allow control of the resulting part chemical composition which also directly affected phase transformation temperatures, and related phase structures. The laser process parameters were found to have a significant effect (p < 0.01) on the martensite start/finish temperature, austenite start/finish temperatures, and the total temperature span. The volumetric energy density was also found to have a direct correlation with both the cooling (r = 0.52) and heating (r = 0.53) enthalpies, which was found to be due to increased nickel evaporation. Such control of phase change properties afforded from L-PBF is important for many of the end applications for nitinol components including within the energy and precision actuation sectors.